Occurence of Southern bean mosaic virus (SBMV) in Togo and its interaction with some cowpea cultivars - Gumedzoe, M.Y.D.; Thottappilly, G.; Asselin, A. (1996)
Cowpea (Vigna unguiculata L. Walp) is one of the major grain legumes in tropical Africa. This leguminous plant is susceptible to many diseases including those caused by viruses. This article reports results from surveys conducted from the main cowpea producing areas in Togo for the occurrence of Southern Bean Mosiac Virus (SBMV) and search for cowpea cultivars that are resistant to this virus. Serological tests (double diffusion agarose gel and DAS-ELISA) with Polyclonal antiserum to intact SBMV were used for the identification of the SBMV isolates. Results indicated that SBMV is widespread in the main cowpea producing areas in Togo. Cassia hirsute, naturally infected by SBMV, may constitute a carryover hosts for SBMV between two cowpea growing seasons. Two SBMV isolates (18-10 and 10-19) cloned by local lesions transfers on susceptible cowpea were used for the screening of 58 cowpea cultivars. Cowpea cultivars IT82D-703, IT82D-786, IT83S-818, TVx1193-9F and TVx1850-01E were resistant to both isolates. These resistant cowpea cultivars could be recommended for farmers where SBMV is a serious problem for cowpea production.